Anxiety by COVID-19 Death Reports: Explanatory Study among Jakarta’s Muslim Young Adults - Marta, Rustono Farady; Kurniasari, Nani; Salim, Mufid; Widaningsih, T. Titi; Gatcho, Al Ryanne Gabonada (Mediator: Jurnal Komunikasi, 2023)
The convergence of technology has led to a mass appearance in digital users worldwide. News media must also distribute their news broadcasts using the new advanced technology. In addition, the initial lethality of COVID-19 has led Indonesians astray with the chaos at the beginning of the pandemic. The research aims to identify how COVID-19 news exposure by Republika.co.id can affect the increased anxiety levels of Jakarta’s young adults aged 15-24 years old. Quantitative research uses a positivistic paradigm and a survey method to collect the primary data, whereas secondary data is collected through past surveys related to the study. The collected data will then be tested for validity and reliability before both data variables are tested with the Correlation Test and Coefficient Determination Test. The research results with 100 respondents implicate that the COVID-19 Pandemic news exposure by Republika.co.id is highly correlated to the increase of anxiety levels of Jakarta’s young adults. The effect of this exposure is based at 23,6%, which is a moderate level. The other 76,4% causing the increase in anxiety levels were external factors that were excluded from this research topic.